2009
DOI: 10.1525/si.2009.32.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants' Identity Negotiations and Coping with Stigma in Different Relational Frames

Abstract: This research describes strategies that immigrants deploy in face‐to‐face interactions with indigenous locals and links these strategies to their relational frames and networks. By focusing on interconnections between identity management and network management, the author further explores some of the key trends already documented in the contemporary literature on ethnicity. The article also adds new insight to the analysis of stigma and identity by showing how self‐friend and self‐stranger relationships presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…black and white racial conceptions in the USA), understandings of authenticity and stigmatized identities. While negative connotations of Albanian ethnicity and Islam proliferate, the ability to put forth Italian face(t)s of identity interacts both with a reality of European origin and perceived physical ethnoracial markers (as in the case of Bosnian migrants in Norway, see Valenta 2009). Moving beyond this specific case, one may ask: Why would Pakistani restaurant owners on Brick Lane, London title their restaurants 'Indian' establishments?…”
Section: Discussionmentioning
confidence: 99%
“…black and white racial conceptions in the USA), understandings of authenticity and stigmatized identities. While negative connotations of Albanian ethnicity and Islam proliferate, the ability to put forth Italian face(t)s of identity interacts both with a reality of European origin and perceived physical ethnoracial markers (as in the case of Bosnian migrants in Norway, see Valenta 2009). Moving beyond this specific case, one may ask: Why would Pakistani restaurant owners on Brick Lane, London title their restaurants 'Indian' establishments?…”
Section: Discussionmentioning
confidence: 99%
“…Their cultural distance and lack of Korean language skills also restricted social relationships with Koreans. Immigrant studies highlight how members of an ethnic group experience varying degrees of discrediting and discriminatory practices in their daily interactions with mainstream society (Colic‐Peisker & Walker, ; Hurtado et al., ; Valenta, ). This research also found that participants experienced diverse forms of discrimination against foreigners, particularly those who are from developing countries.…”
Section: Methodsmentioning
confidence: 99%
“…This research also found that participants experienced diverse forms of discrimination against foreigners, particularly those who are from developing countries. Such negative experiences may have influenced immigrants' self‐concept about their ethnicity and resulted in their reluctance to interact with Koreans (Valenta, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, negative stigmas related to obesity (Brewis, Wutich, Faletta-Cowden, & Rodiguez-Soto, 2011), smoking (Stuber, Galea, & Link, 2009), homelessness (Roschelle & Kaufman, 2004), immigrants (Valenta, 2009), HIV=AIDS (Monjok, Smesny, & Essien, 2009;Niehaus, 2007), sexuality (Kaufman & Johnson, 2004), voluntary childlessness (Park, 2002), and felons (Copenhaver, Edwards-Willey, & Byers, 2007) represent only a few articles published in the recent past. Through widely disparate topics studied across nations and cultures, each researcher notes the problems discredited individuals feel compelled to negotiate.…”
Section: Stigmamentioning
confidence: 99%